2023
DOI: 10.3389/fimmu.2023.1062045
|View full text |Cite
|
Sign up to set email alerts
|

A review of TSHR- and IGF-1R-related pathogenesis and treatment of Graves’ orbitopathy

Abstract: Graves’ orbitopathy (GO) is an organ-specific autoimmune disease, but its pathogenesis remains unclear. There are few review articles on GO research from the perspective of target cells and target antigens. A systematic search of PubMed was performed, focusing mainly on studies published after 2015 that involve the role of target cells, orbital fibroblasts (OFs) and orbital adipocytes (OAs), target antigens, thyrotropin receptor (TSHR) and insulin-like growth factor-1 receptor (IGF-1R), and their corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 117 publications
0
5
0
2
Order By: Relevance
“…The activation of TSHR and IGF-1R by their respective autoantibodies (TSH and IGF-1) in OFs of GO initiates a cascade of events, including OF proliferation, inflammatory cytokine production, and HA secretion. These processes contribute significantly to the development of orbital tissue edema and inflammation [ 24 , 25 ]. Our identification of elevated TSHR and IGF-1R expression in GO-OFs aligns with prior research, emphasizing the central roles of these receptors in the pathogenesis of GO [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of TSHR and IGF-1R by their respective autoantibodies (TSH and IGF-1) in OFs of GO initiates a cascade of events, including OF proliferation, inflammatory cytokine production, and HA secretion. These processes contribute significantly to the development of orbital tissue edema and inflammation [ 24 , 25 ]. Our identification of elevated TSHR and IGF-1R expression in GO-OFs aligns with prior research, emphasizing the central roles of these receptors in the pathogenesis of GO [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These processes contribute significantly to the development of orbital tissue edema and inflammation [ 24 , 25 ]. Our identification of elevated TSHR and IGF-1R expression in GO-OFs aligns with prior research, emphasizing the central roles of these receptors in the pathogenesis of GO [ 24 , 26 ]. Notably, a study [ 27 ] reported a subpopulation of cells exhibiting the CD34+Col1+ phenotype within the orbit of GO during flow cytometric analysis, which suggests that the TSHR + subpopulation of GO-OFs might represent CD34 + fibrocytes originating from peripheral blood mononuclear cells (PBMCs).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins were previously shown to contribute to GO pathogenesis. 36 Therefore, IRE1 and autophagy can play essential roles in both SMAD-dependent and SMAD-independent signaling pathways in GO orbital fibroblasts. Unlike SMAD2, SMAD3 and SMAD4 did not show significant expression differences.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid eye disease (TED) is an extrathyroidal manifestation of GD [ 5 , 6 , 7 , 8 ]. Studies show that TED occurs in 13–69% of GD cases [ 9 , 10 ]. Similar to GD, TED is caused by an autoimmune response.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to GD, TED is caused by an autoimmune response. The pathophysiology underlying TED is complex, with key factors being the infiltration of activated T and B lymphocytes, activation of orbital fibroblasts (OFs), and the presence of autoantibodies targeting a common autoantigen (i.e., TSHR) expressed in thyroid and orbital tissues [ 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 ]. In TED, TSHR receptor antibodies (TRABs) and antibodies to insulin-like growth factor 1 receptor (anti-IGF-1R) interact with OFs.…”
Section: Introductionmentioning
confidence: 99%